Assessing the impact of business uncertainty on supply chain integration. Issue 2 (8th August 2016) - Kim, Minkyun; Chai, Sangmi
Abstract : Purpose: The main objective of this study is to investigate how business uncertainty affects the implementation of supply chain integration. More importantly, this research divides business uncertainty into four dimensions and supply chain integration into three dimensions to examine the role of each dimension. In addition, it investigates the moderating effects of manufacturing approaches, such as push and pull, in the relationship between supply chain integration and performance. Design/methodology/approach: Through a structured survey, this study collected 259 responses from supply executives, and supply and purchasing managers of US manufacturing firms. The empirical data analysis was done by using the partial least squares technique. Findings: The results empirically support the findings that business uncertainty positively affects implementation of supply chain integration. Among the four dimensions of business uncertainty, dynamism and hostility significantly affect implementation of internal integration, integration with suppliers, and integration with customers. In addition, manufacturing approaches, such as push and pull, have a moderating effect on the relationship between supply chain integration and performance. Practical implications: This study collected survey responses from a manufacturing firm in the supply chain to assist managers to find a solution while dealing with business uncertainty through the implementation of supply chain integration. It also emphasizes manufacturing approaches, such as push and pull, in implementing supply chain integration to improve performance. Thus, supply and purchasing managers should consider the business uncertainty that they are dealing with while developing their supply chain strategy. Originality/value: To the best of our knowledge, this study is the first to provide meaningful insights on the effects of supply chain integration toward dealing with business uncertainty. More importantly, by dividing the dimensions of business uncertainty and supply chain integration, this study presents empirical evidence of the significant role of supply chain practices in uncertain business conditions. In addition, this study addresses the gap in extant literature and shows that managers need to consider their manufacturing approach in supply chain integration to improve business performance.